Peranan Keputusan Investasi dan Pendanaan Pengaruhnya Terhadap Nilai Perusahaan Melalui Kinerja Keuangan - AINUN JARIAH (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
Abstract Enterprise value is important to the company because it describes the welfare of the owner. Implementation of prudent and appropriate financial management functions will have an impact on company value. Financial decisions in the view of financial management include investment decisions, funding, and dividends. This study aims to determine the effect of investment decisions and funding decisions directly and indirectly, partially or simultaneously to the financial performance and value of manufacturing companies in Indonesia. The number of samples is 22 consumer goods manufacturing companies that routinely publish financial reports during the study period. The results showed that partially only investment decisions that affect the financial performance and corporate value. Simultaneously significant effect on financial performance and firm value. The value of multiple correlation coefficient (R) is 0.953 with significance 0.000, which means there is significant relationship with firm value. While the value of determination coefficient (R square) of 0.908 or 90.8% means investment decisions and financing decisions are able to explain the effect on corporate value variables together 90.8% and the rest of 9.2% explained by other variables.